Evaluating Care in Patients with Delirium and Dementia in a Busy District General Hospital: An Audit - Muhammad Bilal Saleem; Nataliia Vilinska; Susan Hay (BJPsych Open)
Aims: Delirium is defined as the acute confusional state common in the elderly patient population of hospitals. Alongside existing diagnosed and undiagnosed dementia, it is a common cause of cognitive impairment in the elderly. This project aimed to evaluate the care patients with delirium and dementia received by analysing interventions made by both the referring party and the liaison team as per the local and national guidelines.